Effectiveness of Discovery Learning Model Assisted by Interactive Video to Improve Science Literacy of Elementary School Students - Rani Rahayu; Fadhilah Khairani (Program Doktor Pendidikan FKIP Universitas Lampung, 2025)
The problem in this study is the low science learning outcomes of fourth grade elementary school students. This study aims to analyse and describe the effect of discovery learning model assisted by video media on science learning outcomes of fourth grade students of SD Negeri 2 Bulurejo. The method in this research is a pseudo-experiment with a non-equivalent control group design. The population of this study were all fourth grade students totalling 48 students. Determination of the sample of this study using purposive sampling technique, namely sampling with certain considerations. The sample consisted of class IVA as the control class and class IVB as the experimental class. Data collection techniques in this study used tests and non-tests in the form of observations to observe student activity. The data analysis used was simple linear regression test. The results of the study concluded that there was a significant effect of the discovery learning learning model assisted by video media on the science learning outcomes of fourth grade students of SD Negeri 2 Bulurejo in the 2021/2022 academic year.